Volodymyr Kyrychenko (17.06.1942 - 02.04.2019) (Algebra and Discrete Mathematics, 2019)
Volodymyr Kyrychenko has gone on April 2, 2019. Student of A. V. Roiter and D. K. Faddeev, Volodymyr Kyrychenko was among the pioneers of the Kyiv school of the Theory of Representations and significantly contributed in its forming and achievements. His papers on lattices and orders, on serial and semidistributive rings has become classical in these areas. His book “Finite Dimensional Algebras” (with Yuriy Drozd) remains number one both as a manual for students and as a monograph. His trilogy “Algebras, Rings and Modules” (with Nadya Gubareni and Michiel Hazewinkel) has gained wide popularity.